When Blue-Collars Feel Blue: Depression and Low Occupational Grade as Synergistic Predictors of Incident Cardiac Events in Middle-Aged Working Individuals. (February 2017) - Lemogne, Cédric; Meneton, Pierre; Wiernik, Emmanuel; Quesnot, Ariane; Consoli, Silla M.; Ducimetière, Pierre; Nabi, Hermann; Empana, Jean-Philippe; Hoertel, Nicolas; Limosin, Frédéric; Goldberg, Marcel; Zins, Marie
Abstract : Background—: The association of psychological variables with cardiovascular health might depend on socioeconomic status. We examined the moderating effect of occupational grade on the association between depression and incident cardiac events among middle-aged workers from the GAZEL cohort. Methods and Results—: A total of 10 541 participants (7855 men, mean age: 47.8±3.5 years) free of cardiovascular diseases completed the Center of Epidemiologic Studies Depression scale in 1993. Age, sex, and occupational grade (low, medium, and high) were obtained from company records. Classical cardiovascular risk factors were self-reported. All participants were followed-up for medically certified cardiac events from January 1994 to December 2014. Associations between baseline variables and incident cardiac events were estimated with hazard ratios and 95% confidence intervals computed in Cox regressions. After a median follow-up of 21 years, 592 (5.6%) participants had a cardiac event. There was a significant interaction between depression and occupational grade in both age- and sex-adjusted ( P =0.008) and multiadjusted ( P =0.009) models. This interaction was mainly explained by an association between depression and incident cardiac events that prevailed among participants of low occupational grade (3.71 versus 1.96 events per 1000 person-years among those depressed versus nondepressed, multiadjusted hazard ratios [95% confidence intervals], 1.99 [1.12–3.48]). Conclusions—: From a research perspective, these results may account for previous conflicting results and constitute an impetus for reanalyzing previous data sets, taking into account the moderating role of socioeconomic status. From a clinical perspective, they urge clinicians and policy makers to consider depressive symptoms and low socioeconomic status as synergistic cardiovascular risk factors. Abstract : Supplemental Digital Content is available in the text.